Fishmeal supplementation during ovine pregnancy and lactation protects against maternal stress-induced programming of the offspring immune system. Issue 1 (December 2015) - Fisher-Heffernan, Rebecca; Or'Rashid, Mamun; AlZahal, Ousama; Quinton, Margaret; Boermans, Herman; McBride, Brian; Regnault, Timothy; Karrow, Niel
Abstract Background Prenatally stressed offspring exhibit increased susceptibility to inflammatory disorders due toin utero programming. Research into the effects of n-3 PUFAs shows promising results for the treatment and prevention of these disorders. The purpose of this study was to investigate whether maternal fishmeal supplementation during pregnancy and lactation protects against programming of the offspring's immune response following simulated maternal infection. Methods In order to accomplish this, 53 ewes were fed a diet supplemented with fishmeal (FM; rich in n-3 PUFA) or soybean meal (SM; rich in n-6 PUFAs) from day 100 of gestation (gd 100) through lactation. On gd135, half the ewes from each dietary group were challenged with either 1.2 μg/kgEscherichia coli lipopolysaccharide (LPS) endotoxin to simulate a bacterial infection, or saline as the control. At 4.5 months of age the offspring's dermal immune response was assessed by cutaneous hypersensitivity testing with ovalbumin (OVA) andcandida albicans (CAA) 21 days after sensitization. Skinfold measurements were taken and serum blood samples were also collected to assess the primary and secondary antibody immune response. Results Offspring born to SM + LPS mothers had a significantly greater change in skinfold thickness in response to both antigens as well as a greater secondary antibody response to OVA compared to all treatments. Conclusions Supplementation during pregnancy with FM appears to protect against adverse fetal programming that may occur during maternal infection and this may reduce the risk of atopic disease later in life.